Optimum Constant-Stress Partially Accelerated Life Test Plans Using Type-I Censored Data from the Inverse Weibull Distribution - Ismail, Ali A.; Al Tamimi, A. (Проблемы прочности, 2017)
In this paper, a constant stress partially accelerated life test (CSPALT) model is presented and analyzed using type-I censored data from the inverse Weibull distribution. The maximum likelihood estimates (point and interval) of the distribution parameters and the acceleration factor are obtained. CSPALT plans are developed. The proportion of test units that should be allocated to run under accelerated condition is optimally determined. To demonstrate the theoretical results, simulation studies are made. Предложенная модель частично ускоренных ресурсных испытаний применена к данным, цензурированным по типу I для обратного распределения Вейбулла. Оценка максимальной вероятности параметров распределения и коэффициента ускорения выполнена в точечном и интервальном видах. Осуществлено планирование ускоренных ресурсных испытаний с оптимизацией доли испытаний, которые необходимо проводить при нормальных эксплуатационных условиях. Численное моделирование тестовой задачи подтвердило точность аналитических расчетов. Запропоновану модель частково прискорених ресурсних випробувань застосовано до даних, цензурованих по типу I для зворотного розподілу Вейбулла. Оцінку максимально ї ймовірності параметрів розподілу і коефіцієнта прискорення виконано в точковому й інтервальному вигляді. Виконано планування прискорених ресурсних випробувань з оптимізацією частки випробувань, які необхідно проводити при нормальних експлуатаційних умовах. Чисельне моделювання тестової задачі підтвердило точність аналітичних розрахунків.